2017
DOI: 10.2147/hmer.s129681
|View full text |Cite
|
Sign up to set email alerts
|

Role of intrafamilial transmission in high prevalence of hepatitis C virus in Egypt

Abstract: Background: Egypt has the highest prevalence of hepatitis C virus (HCV) worldwide. Although an effective HCV treatment program has been adopted, it is estimated that the number of newly reported cases in Egypt is still high. Intrafamilial transmission may play a role in the high prevalence of HCV in Egypt. Identification of risk factors for the transmission of HCV may help in decreasing its prevalence and eliminating its infection. Aim: The aim of this study was to estimate the prevalence of HCV infection amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
5
14
1
Order By: Relevance
“…Further research is required to understand why infection clusters at the village and household levels. In households, there is a range of possible factors, including sexual transmission, sharing razors or using the same barber or healthcare provider with poor infection control practices [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to understand why infection clusters at the village and household levels. In households, there is a range of possible factors, including sexual transmission, sharing razors or using the same barber or healthcare provider with poor infection control practices [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Our study found an association between familial history of viral hepatitis and HCVAb prevalence. Previous observational studies have reported clustering of cases within households and documented evidence of higher disease prevalence among individuals with an infected family member compared to the general population [20][21][22][23] . Moreover, a recent cross-sectional survey of HCV patients conducted in China showed that long term exposure to an infected family member was associated with infection 24 , an indication that a constant exposure to low-risk transmission routes such as razors, tooth brushes and nail clippers could still contribute to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found an association between familial history of viral hepatitis and HCVAb prevalence. Previous observational studies have reported clustering of cases within households and documented evidence of higher disease prevalence among individuals with an infected family member compared to the general population [19][20][21][22] . Moreover, a recent cross-sectional survey of HCV patients conducted in China showed that long term exposure to an infected family member was associated with infection 23 , an indication that a constant exposure to low-risk transmission routes such as razors, tooth brushes and nail clippers could still contribute to infection.…”
Section: Discussionmentioning
confidence: 99%